Death related to nicotine replacement therapy: A case report. (April 2020) - Tjoncke, J-A.; Goncalves, R.; Castaing, N.; Molimard, M.; Tovagliaro, F.; Titier, K.
Highlights: Nicotine substitution therapies can be fatal if misused. Transdermal absorption of nicotine induces a gradual symptomatology and an agony. Importance of supervising nicotine substitution therapy in detention. Toxicological analyses are absolutely necessary in nicotine poisoning cases. Abstract: Transdermal nicotine patches and nicotine tablets are widely used for substitution therapies after cessation of smoking. Toxic concentrations of nicotine and cotinine, its main metabolite, are rarely reported, either in cases of misuse or in a fatal context. We report here a rare fatal case due to massive exposure to nicotine replacement therapy. A 41-year-old man was found dead by his cellmate with 7 nicotine patches on the body. There were 14 nicotine patches (21 mg) and 5 empty blisters of nicotine tablets (Nicopass® 1.5 mg) in the bin. External, internal, and histological examinations revealed asphyxia syndrome. Toxicological analyses indicated lethal concentrations of nicotine and cotinine in femoral (2239 and 1230 ng/mL) and cardiac blood (1344 and 1090 ng/mL). Screening for ethanol, drugs, and illicit drugs revealed therapeutic concentrations of cyamemazine, lormetazepam, nordiazepam, oxazepam, and buprenorphine and its metabolite. THC and its metabolites were also detected, reflecting use of cannabis. The findings highlight the risk of nicotine poisoning in persons using nicotine patches. This case emphasises the importance of carrying out complete toxicological analyses to prevent other instances of nicotine poisoning from being overlooked.